Pengaruh Umur Telur Tetas Itik Mojosari dengan Penetasan Kombinasi terhadap Fertilitas dan Daya Tetas - Neka Meliyati; Khaira Nova; Dian Septinova (JURNAL ILMIAH PETERNAKAN TERPADU, 2012)
Hatching can be done naturally and artificially or by way of combining them.  The advantage is that it can produce hatching combined fertility and hatchability higher.  One of the factors that affect fertility, weight loss, hatchability, and hatching weight are age of hatching eggs. The purpose of this study were 1) determine the effect of age mojosari duck hatching eggs with hatching combination on fertility, weight loss, hatchability, and hatching weight, 2) determine the age of the best hatching eggs from hatching eggs mojosari duck with combinations on fertility, hatchability losses, hatchability, and hatching weight. This study used completely randomized design with 3 treatments age of hatching eggs (1, 4, and 7 days) and repeat 6 times.  Duncan test done if there is a real variable. The results showed significant effect (P <0.05) at the age of hatching eggs (1, 4, and 7 days) on fertility and not significant (P> 0.05) to weight loss, hatchability, and hatching weight. Age of hatching eggs one day produce the best fertility (91.67%) compared to the age of 4 days of hatching eggs (83.33%, and 7 days (72.92%). Keywords: combination of hatching, age Mojosari duck hatching eggs, fertility, hatchability